1996
DOI: 10.1111/j.1540-6288.1996.tb00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence on Foreign Exchange Market Efficiency: An Application of Cointegration Tests

Abstract: This study extends and expands the body of evidence related to foreign exchange market efficiency by employing the single‐equation cointegration test proposed by Phillips and Ouliaris [19], and the Johansen [12] 1991 Full Information Maximum Likelihood procedure for a system of equations. Through the use of these updated techniques and a global data set, the authors are able to more carefully test for the presence of cointegrating relationships and examine the consistency of the results in three trading locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Like Sephton and Larsen, they argue that asset prices may be cointegrated due to model misspecification, and Lajaunie and Naka (1997) find cointegration to be sensitive to the sample period. Rush (1989, 1991), Lajaunie, Mcmanis, and Naka (1996), Lajaunie and Naka (1992), and Coleman (1990) do not find any cointegration and thus conclude that markets are weak form efficient, a conclusion contradicted by Wu and Chen (1998).…”
Section: Foreign Exchange Market Efficiencymentioning
confidence: 73%
See 1 more Smart Citation
“…Like Sephton and Larsen, they argue that asset prices may be cointegrated due to model misspecification, and Lajaunie and Naka (1997) find cointegration to be sensitive to the sample period. Rush (1989, 1991), Lajaunie, Mcmanis, and Naka (1996), Lajaunie and Naka (1992), and Coleman (1990) do not find any cointegration and thus conclude that markets are weak form efficient, a conclusion contradicted by Wu and Chen (1998).…”
Section: Foreign Exchange Market Efficiencymentioning
confidence: 73%
“…The Johansen (1991) cointegration test procedure is appropriate for systems of higher numbers of variables (Lajaunie et al, 1996). The test statistics used are the trace statistic and maximal eigenvalue (k-max) test.…”
Section: Johansen Testsmentioning
confidence: 99%
“…Baillie and Bollerslev (1989), however, find common stochastic trends in a sample of seven exchange rates, whereas, contrary to the two other authors, they apply the multivariate Johansen procedure. Coleman (1990), Copeland (1991), Tronzano (1992), Lajaunie and Naka (1992), Diebold, Gardeazábal, and Yilmaz (1994), Lajaunie, Naka, and McManis (1996), and Rapp and Sharma (1999) cannot detect cointegration of exchange rates for periods up to the end of the 1990s. On contrary, Alexander and Johnson (1992), Masih and Masih (1994) and Crowder (1994) can find long-run relationships among exchange rates on a US dollar basis and Karfakis and Parikh (1994) on the basis of the Australian dollar.…”
Section: Introductionmentioning
confidence: 86%
“…Among other econometric techniques, a cointegration analysis has been employed by several recent studies to examine foreign exchange market efficiency. The majority of prior empirical work (e.g., Coleman, 1990;Copeland, 1991;Lajaunie, McManis, & Naka, 1996;Lajaunie & Naka, 1992;MacDonald & Taylor, 1989;Rapp & Sharma, 1999) has found that spot exchange rates for various major currencies generally are not cointegrated during the modern float. The absence of cointegration and thus a cointegrating vector and the error correction model (ECM) (e.g., Engle & Granger, 1987) implies that the current value of one currency cannot be predicted by past values of other currencies.…”
Section: Introductionmentioning
confidence: 99%